Pengembangan Perangkat Pembelajaran Berbasis Subject Specific Pedagogy (SSP) Terintegrasi Pendidikan Karakter dan Revolusi Mental untuk SD/MI di Bandarlampung - Nurul Hidayah (Institut Agama Islam Negeri (IAIN) Curup, 2018)
This study aims to: 1) developing a learning device integrates character education and mental revolution based of Subject Specific Pedagogy (SSP) for Vocabulary School in Bandar Lampung; 2) describe the learning device feasibility integrated character education and mental revolution based of Subject Specific Pedagogy (SSP) for Vocabulary School in Bandar Lampung; and 3) determine the achievement of learning. This research is conducted with the design of Research and Development, ie research which seeks to design and create prototype learning device with certain specifications. Subjects SDN 1 Constable, SDN 1 Kaliawi, and SDN 2 Sumur Batu. The procedures of research data analysis are: 1) tabulate data from questionnaires and interviews; 2) analyze data on the tabulation; 3) interpret results tabulation; 4) concluded; and 5) analyzing the data obtained from the survey results. Research results : 1) Development is done using a seven-step Research and Development has produced a learning device Indonesian sixth grade elementary school-based Subject Specific Pedagogy (SSP) integrates character education; 2) The quality of products developed learning device gain value with excellent category; 3) The achievement of learning outcomes in most aspects of high character is honest, curiosity, discipline, and hard work.